A novel neurotensin/xenin fusion peptide enhances β-cell function and exhibits antidiabetic efficacy in high-fat fed mice. Issue 8 (27th August 2021) - Perry, Rachele A.; Craig, Sarah. L.; Gault, Victor A.; Flatt, Peter R.; Irwin, Nigel
Abstract: Neurotensin and xenin possess antidiabetic potential, mediated in part through augmentation of incretin hormone, glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP), action. In the present study, fragment peptides of neurotensin and xenin, acetyl-neurotensin and xenin-8-Gln, were fused together to create Ac-NT/XN-8-Gln. Following assessment of enzymatic stability, effects of Ac-NT/XN-8-Gln on in vitro β-cell function were studied. Subchronic antidiabetic efficacy of Ac-NT/XN-8-Gln alone, and in combination with the clinically approved GLP-1 receptor agonist exendin-4, was assessed in high-fat fed (HFF) mice. Ac-NT/XN-8-Gln was highly resistant to plasma enzyme degradation and induced dose-dependent insulin-releasing actions ( P <0.05 to P <0.01) in BRIN-BD11 β-cells and isolated mouse islets. Ac-NT/XN-8-Gln augmented ( P <0.001) the insulinotropic actions of GIP, while possessing independent β-cell proliferative ( P <0.001) and anti-apoptotic ( P <0.01) actions. Twice daily treatment of HFF mice with Ac-NT/XN-8-Gln for 32 days improved glycaemic control and circulating insulin, with benefits significantly enhanced by combined exendin-4 treatment. This was reflected by reduced body fat mass ( P <0.001), improved circulating lipid profile ( P <0.01) and reduced HbA1c concentrations ( P <0.01) in the combined treatment group. Following an oral glucose challenge, glucose levels were markedly decreased ( P <0.05) only in combination treatment group and superior to exendin-4 alone, with similar observations made in response to glucose plus GIP injection. The combined treatment group also presented with improved insulin sensitivity, decreased pancreatic insulin content as well as increased islet and β-cell areas. These data reveal that Ac-NT/XN-8-Gln is a biologically active neurotensin/xenin fusion peptide that displays prominent antidiabetic efficacy when administered together with exendin-4.